¿Does melatonin treatment during lactation influence milk production in Lacaune and Aáaf ewes? - Abecia, J.A.=700 1 Forcada, F.; Valares, J.A.; Palacin, I.; Martin, S.; Martino, A.; Gomez, M.I.; Palacios, C.
(Es, En)
ilus., 25 ref.
Keywords: OVINOS; FERTILIDAD; REPRODUCCION; PRODUCCION LECHERA; MALATONINA; ESPAÑA